READING IRAQ FROM INDONESIA: DIALOGUES BETWEEN IRAQI LITERATURE AND INDONESIAN SOCIOCULTURAL CONTEXTS - Rodiah, Ita (Al-Qalam, 2025)
This study addresses a critical gap in global literary discourse, the near absence of Southeast Asian perspectives in interpreting Arab post-secular fiction. While Iraqi literature is often analyzed within Middle Eastern frameworks, this study argues for a necessary transregional approach. Focusing on Inaam Kachachi’s Tashari, it examines how the Christian-Iraqi protagonist, Wardiyah Iskandar, whose narrative embodies sacred agency, ritual memory, and moral dislocation, resonates ethically and affectively within Indonesia’s pluralistic, post-authoritarian, and culturally contested context. The study aims to: (1) analyze the reinterpretation of Iraqi post-secular narratives through Indonesia’s sociocultural and religious context; (2) reveal ethical and spiritual rearticulations emerging from transregional encounters; and (3) reframe Arab trauma fiction through Southeast Asian hermeneutics. Methodologically, it adopts an interdisciplinary qualitative approach combining post-secular literary theory, sociocultural analysis, and comparative hermeneutics. A close reading of Tashari is conducted alongside Indonesia’s discourses on interfaith pluralism, spiritual fragmentation, and moral reformulation. The dialogic mapping reveals interpretive pathways neglected by dominant paradigms. The findings show that Tashari functions as a transregional ethical archive, a literary space where theological boundaries blur, interfaith solidarities form, and sacred dissent emerges. Indonesian readers, shaped by histories of colonialism, authoritarianism, and religious negotiation, actively reconstruct the novel’s moral and spiritual meanings, transforming Iraqi suffering into a shared space of ethical reflection and collective mourning. This study proposes a new model of transregional literary ethics, demonstrating how post-secular fiction mediates cross-cultural understanding, rehumanizes the other, and generates transformative moral and spiritual resistance across contested geographies.